GALERI BUDAYA DAYAK BAKUMPAI DI MARABAHAN - Ananda, Rela Dhea; Mentayani, Ira (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
Culture is very important to be preserved, but there are some obstacles that must be followed up. One of them is the lack of attention of the younger generation to the history and culture of the region. Efforts are needed to provide awareness to the younger generation that it is important to preserve their own culture. One of the cultural preservation efforts is to provide a space for expression and appreciation to broaden horizons by applying technology from several digital media through video, sound, simulation, hologram, animation, and other visual effects. The design of the Bakumpai Dayak cultural gallery in Marabahan is a form of preservation using the Linguistic Analogy method and the concept of Contemporary Architecture. This cultural gallery functions as a medium of information about the history of the Bakumpai Dayak culture by making technology the main tool that plays an important role in this design.